2018
DOI: 10.1186/s40168-018-0546-9
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomics reveals a differential temperature effect on the structural and functional organization of the anaerobic food web in rice field soil

Abstract: BackgroundThe expected increase in global surface temperature due to climate change may have a tremendous effect on the structure and function of the anaerobic food web in flooded rice field soil. Here, we used the metatranscriptomic analysis of total RNA to gain a system-level understanding of this temperature effect on the methanogenic food web.ResultsMesophilic (30 °C) and thermophilic (45 °C) food web communities had a modular structure. Family-specific rRNA dynamics indicated that each network module repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 84 publications
(94 reference statements)
2
30
0
Order By: Relevance
“…The functions of these different taxa within the methanogenic degradation process are unclear, but most probably involve various hydrolytic and fermentation processes. Helicobacteraceae , for example, may be involved in anaerobic oxidation of propionate, possibly even acetate ( Noll et al, 2010 ; Sattley and Madigan, 2014 ; Liu et al, 2018 ; Peng et al, 2018 ). The different bacterial taxa were separated together with archaeal taxa into three major network modules, the most distinct being those in soils exposed to 45°C versus those exposed to moderate temperatures (either 25 or 35°C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions of these different taxa within the methanogenic degradation process are unclear, but most probably involve various hydrolytic and fermentation processes. Helicobacteraceae , for example, may be involved in anaerobic oxidation of propionate, possibly even acetate ( Noll et al, 2010 ; Sattley and Madigan, 2014 ; Liu et al, 2018 ; Peng et al, 2018 ). The different bacterial taxa were separated together with archaeal taxa into three major network modules, the most distinct being those in soils exposed to 45°C versus those exposed to moderate temperatures (either 25 or 35°C).…”
Section: Discussionmentioning
confidence: 99%
“…This change often coincides with a change in the methanogenic pathway from a mixture of acetoclastic plus hydrogenotrophic to exclusively hydrogenotrophic methanogenesis, and by the replacement of acetoclastic methanogenesis by syntrophic acetate oxidation that is coupled to hydrogenotrophic methanogenesis ( Conrad et al, 2009 ; Liu and Conrad, 2010 ; Rui et al, 2011 ). Recently, metatranscriptomics and co-occurrence network analysis revealed that the microbial community of Italian rice field soil consisted of modules characterized by the functional activities of polymer hydrolysis, syntrophic oxidation of key intermediates, and methanogenesis ( Peng et al, 2018 ). Both mesophilic (30°C) and moderate thermophilic (45°C) temperatures had a differential effect on all the functional activities ( Peng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acetate consumption could have occurred via SAO (e.g., by members of the classes Synergistia or OPB54 (Firmicutes) [60]), or could have been assimilated by acetogens and hydrogenotrophic methanogens to build biomass. The order Thermoanaerobacterales (class Clostridia) was present in lower abundance (3% in T6), with its dynamic behavior in the second stage reaching similar levels as in the inoculum.…”
Section: Microbial Community Structure and Dynamicsmentioning
confidence: 99%
“…However, not all genes are expressed at any given time, and DNA extracted from soil can also represent dormant, or dead, populations that are not contributing to any given function. The soil metatranscriptome has been used to determine functions that are expressed by members of the soil microbiome ( Tveit et al, 2014 ; Hultman et al, 2015 ; Jiang et al, 2016 ; Peng et al, 2018 ; Roy Chowdhury et al, 2019 ). However, these studies generally rely on relatively shallow metatranscriptomes, with a read depth that is insufficient to cover all the members of the community and therefore only queries the most abundant and transcriptionally active species and genes.…”
Section: Introductionmentioning
confidence: 99%